Successful management of proliferative glomerulonephritis with monoclonal immune deposits with combined immunosuppressive therapy. Issue 1 (7th December 2018) - Maan, Dipesh; Clark, Barbara; Bunker, Mark; Arora, Swati
Abstract : Proliferative glomerulonephritis with monoclonal immune deposits (PGNMID) is a newly described entity characterised by monoclonal IgG deposits consisting of single light chain isotype and single heavy chain subtype (IgG1-4) in the kidneys. We are presenting two cases of patients who presented with acute kidney injury and worsening proteinuria. Kidney biopsy showed membranoproliferative pattern. Special staining for subclass of IgG showed monoclonal IgG3-kappa (case 1) and IgG1-kappa deposits (case 2) suggestive of PGNMID. Workup for underlying infection, malignancy, monoclonal gammopathy was negative. Since pathogenesis of PGNMID involves clonal proliferation of B-cells, we treated both patients with rituximab along with steroids that led to improvement of proteinuria and renal function. We also reviewed current literature to assess efficacy of rituximab in treatment of PGNMID. However, a larger pool of patients and a longer follow-up period is required to establish a role of rituximab and steroids in the treatment of this disease entity.